Usability, Usefulness, and Desirability of Learning Activities for Sexual Health Education for Individuals with Intellectual and Developmental Disabilities. Issue 3 (3rd July 2021) - Schmidt, Elizabeth K.; Dougherty, Megan; Robek, Natalie; Darragh, Amy; Hand, Brittany N.; Havercamp, Susan M.; Weaver, Lindy L.; Sommerich, Carolyn
Abstract: Sexuality education (SE) for individuals with intellectual and developmental disabilities is needed, but is sparse. Seven individuals with intellectual and developmental disabilities and two educators participated in a mixed method participatory design to iteratively refine nine learning activities for SE. We analyzed usability, usefulness, and desirability of each activity. The utilization of multiple modalities, experiential learning opportunities, and inclusion of different perspectives yielded nine learning activities that were usable, useful, and desirable. This work resulted in learning activities to improve accessibility of SE for individuals with I/DD. Additional research is needed to evaluate activity effectiveness in improving knowledge.